Evaluating the Long-term Safety and Efficacy of Intralesional Statins versus Corticosteroids in the Treatment of Hypertrophic Scars: A Randomized Controlled Trial" Justification - Shree, Anu; Sinha, Keshav Kumar (Student’s Journal of Health Research Africa, 2024)
Background Hypertrophic scars (HTS) are fibrotic dermal disorders marked by excessive collagen accumulation subsequent to dermal injury. Triamcinolone acetonide is a commonly employed corticosteroid in the management of hypertrophic scars, yet its application is linked to complications including skin atrophy and pigmentary alterations. Statins, recognized for their antifibrotic and anti-inflammatory properties, offer a potential alternative with reduced adverse effects. Objective: This study sought to assess and contrast the long-term safety and efficacy of intralesional statins with corticosteroids (Triamcinolone acetonide) in the management of hypertrophic scars. Methods A randomized controlled trial was performed at the Department of Plastic Surgery, Patna Medical College and Hospital, Patna. Sixty patients aged 10 to 50 years with hypertrophic scars of less than 5 years’ duration were randomized into two groups: Group A (n=30) received intralesional Triamcinolone acetonide, while Group B (n=30) received intralesional simvastatin. Injections were given at three-week intervals, totaling five sessions. Scar assessment was conducted utilizing the Vancouver Scar Scale (VSS) at baseline, 6 weeks, 3 months, 6 months, and 12 months. Results Both groups exhibited a statistically significant decrease in VSS scores over time (p<0.05). Group B (statin) exhibited a more expedited enhancement, especially in vascularity and pliability metrics. At 12 months, the recurrence rate in the statin group was 20%, whereas in the corticosteroid group it was 36.7%. Adverse effects were negligible in both groups, comprising transient erythema and mild discomfort at the injection site. Conclusion Intralesional statins seem to be a viable alternative to corticosteroids for the management of hypertrophic scars, demonstrating similar efficacy with a potentially superior safety profile. It is advisable to conduct larger studies with prolonged follow-up to corroborate these findings.